Use of Mobile Instant Messaging Applications for Readers Service Delivery in University libraries in South-South, Nigeria. - Ofua, Justice Owajeme; Ngwuchukwu, Margaret Nwakaego (Communicate: Journal of Library and Information Science, 2025)
This study investigates librarians’ use of mobile instant messaging applications for readers’ service delivery in university libraries in South-South Nigeria. The study adopted a descriptive survey research method. The population of the study is 324 librarians from both federal and state university libraries in south-south zone, Nigeria. The sample size for the study is 324, due to the manageable size of the population, the study employed total enumeration sampling technique. Method of data analysis was done using mean and standard deviation to answer all the research question. The study revealed that readers’ services rendered using Mobile Instant Messaging Applications in university libraries in South-South, Nigeria include; user education, loan services, book reservation, announcement/public relation, current awareness services for library resources, selective dissemination of information, reference services, extension services, indexing and abstracting among others. On the second objective, the study also revealed the extent to which the use of Mobile Instant Messaging Applications contributes to effective readers’ service delivery in university libraries in South-South Nigeria is high. The findings will inform other University libraries in developing countries to see the need to integrate mobile instant messaging application in their readers’ services delivery to increased accessibility to a wide range of readers and extending the reach of library services beyond physical boundaries.